A Comparison of Ocular Vestibular Evoked Myogenic Potentials via Audiometric and Nonaudiometric Bone Vibrators - Garbutt, Ruby E.; O'Beirne, Greg A.; Maslin, Michael R. D. (Journal of the American Academy of Audiology, 2023)
Background There is limited evidence demonstrating the ability of audiometric bone vibrators to elicit ocular vestibular evoked myogenic potentials (oVEMPs). The RadioEar B71 bone vibrator has insufficient power output to reliably evoke oVEMPs, which has previously left nonaudiometric and nonmedically approved devices such as the Brüel & Kjær Mini-shaker 4810 as the only feasible alternative. The newer RadioEar B81 model has a higher power output than its predecessor, but evidence for its suitability for eliciting oVEMPs has so far been mixed. This variability may be due to factors other than simply the power output, such as whether sufficient static force is applied to hold the transducer in place and transfer vibratory energy into the bone.Purpose This study aimed to test the hypothesis that bone-conducted oVEMPs can be obtained with the B81 that are equivalent to those from the Mini-shaker, the de facto gold-standard transducer for this response, when the outputs of the two transducers are matched and they are coupled with sufficient static force.Research Design oVEMPs elicited by both transducers were recorded in a counterbalanced within-groups design.Study Sample Sixteen healthy adults (12 female; 22–47 years) with no history of hearing, balance, or neurological disorders were included in the study.Data collection and analysis One-cycle alternating tone-burst stimuli at 500 Hz were delivered to the mastoid from each transducer. The vibratory force levels were matched at 127 dB peak-to-peak equivalent force levels, and both were held in place with a static force around 10 N. oVEMP waveforms were gathered from the contralateral eye using the belly-tendon montage and were assessed for statistical equivalence.Results There was an absence of any statistically significant difference in N10 and N10–P15 amplitudes in oVEMPs from each transducer.Conclusions Our results indicate that B81 can elicit oVEMPs with no meaningful differences to those from the Mini-shaker, provided effective stimulus levels are matched and static force is sufficient. Although further work is necessary to investigate equivalence at other stimulus frequencies and stimulation sites, the results support the use of the B81 to elicit 500Hz oVEMPs at the mastoid in a clinical setting.
Keywords: bone conduction; oVEMP; vestibular evoked myogenic potential; B81; Mini-shaker